Syndrome‐Specific Patterns of Regional Cerebral Glucose Metabolism in Posterior Cortical Atrophy in Comparison to Dementia with Lewy Bodies and Alzheimer's Disease—A [F‐18]‐Fdg Pet Study. Issue 2 (5th March 2014) - Spehl, Timo S.; Hellwig, Sabine; Amtage, Florian; Weiller, Cornelius; Bormann, Tobias; Weber, Wolfgang A.; Hüll, Michael; Meyer, Philipp T.; Frings, Lars
ABSTRACT BACKGROUND Posterior cortical atrophy (PCA) is a rare neurodegenerative syndrome with visuospatial deficits. PET studies have identified hypometabolism of the occipital cortex in PCA. There is, however, a huge overlap in clinical presentation and involvement of the occipital cortex between PCA, dementia with Lewy bodies (DLB), and Alzheimer's disease (AD). Syndrome‐specific patterns of metabolism have not yet been demonstrated that allow for a reliable differentiation with [F‐18]‐FDG‐PET. METHODS A total of 33 dementia patients (PCA n = 6, DLB n = 12, AD n = 15) who underwent [F‐18]‐FDG‐PET imaging and a neuropsychological examination were retrospectively analyzed. Group comparisons of regional cerebral glucose metabolism were calculated with statistical parametric mapping. Extracted clusters were used to evaluate discrimination accuracy by logistic regression. RESULTS PCA patients showed a syndrome‐specific area of hypometabolism in the right lateral temporooccipital cortex. DLB patients showed specific hypometabolism predominantly in the left occipital cortex. Logistic regression based on these two regions correctly separated patients with a sensitivity/specificity of 83/93% for PCA, 75/86% for DLB and 67/78% for AD. Overall accuracy was 73%. CONCLUSION [F‐18]‐FDG‐PET could reveal syndrome‐specific patterns of glucose metabolism in PCA and DLB. Accurate group discrimination in the differential diagnosis of dementia with visuospatial impairment is feasible.